Buried penis; what buried the penis? - Fawzy, Mohamed; Hadidi, Ahmed T. (Frontiers in Pediatrics, 2025)
ObjectivesTo investigate the histological and immuno-histochemical features of dartos fascia in buried penis (BP) as compared to dartos fascia in hypospadias and normal children.Materials and methodsThe study included 40 children, operated on in our center between January 2023 and January 2024. Patients were divided into 3 groups; group A: 13 patients with BP, group B: 14 patients with different grades of distal Hypospadias, and group C with 13 patients who were referred for circumcision (control group). All dartos fascia specimens were blindly examined by the same pathologist. The 3 groups were assessed for histological findings including collagen, elastin, nerve fibers, tactile bodies, fat, smooth muscles.ResultsIn group A (BP), there was statistically significant dominance of thick collagen fibers (thick fibers) p < 0.001, thick smooth muscle fibers (P < 0.001), thick convoluted nerve fibers (p = 0.004) and less fat (P < 0.001) as compared to the hypospadias and control groups. In the hypospadias group, intermediate collagen fibers were the predominant type of fibers (p < 0.001), in addition to long, thin and short thin elastin fibers (p < 0.001) compared to the buried penis and the control groups. The hypospadias group also had significant predominance of chaotic disorganized nonparallel smooth muscle fibers p = 0.003.ConclusionThe fascia in BP is characterized by abnormally thick collagen fibers, thick smooth muscle fibers and thick convoluted nerve fibers. This may explain why the penis is drawn inwards in BP and suggests that it is probably recommended to excise this abnormal fascia during the surgical correction.